Associations Between Core Symptoms of Attention Deficit Hyperactivity Disorder and Both Binge and Restrictive Eating - Kaisari, Panagiota; Dourish, Colin T.; Rotshtein, Pia; Higgs, Suzanne (Frontiers in Psychiatry, 2018)
INTRODUCTION: It is unclear whether core symptoms of ADHD relate to specific types of disordered eating and little is known about the mediating mechanisms. We investigated associations between core symptoms of ADHD and binge/disinhibited eating and restrictive eating behaviour and assessed whether negative mood and/or deficits in awareness and reliance on internal hunger/satiety cues mediate these relationships. METHODS: In two independent studies, we used a dimensional approach to study ADHD and disordered eating. In Study 1, a community-based sample of 237 adults (72.6% female, 18-60 years [M = 26.8, SE = 0.6]) completed an online questionnaire, assessing eating attitudes/behaviours, negative mood, awareness and reliance on internal hunger/satiety cues and ADHD symptomatology. In Study 2, 142 students (80.3% female, 18-32 years [M = 19.3, SE = 0.1]) were recruited to complete the same questionnaires and complete tasks assessing interoceptive sensitivity and impulsivity in the laboratory. RESULTS: In each study, core symptoms of ADHD correlated positively with both binge/disinhibited and restrictive eating and negative mood mediated the relationships. Deficits in awareness and reliance on internal hunger/satiety signals also mediated the association between inattentive symptoms of ADHD and disordered eating, especially binge/disinhibited eating. The results from both studies demonstrated that inattentive symptoms of ADHD were also directly related to binge/disinhibited eating behaviour, while accounting for the indirect pathways of association via negative mood and awareness and reliance on internal hunger/satiety signals. CONCLUSION: This research provides evidence that core symptoms of ADHD are associated with both binge/disinhibited eating and restrictive eating behaviour. Further investigation of the role of inattentive symptoms of ADHD in disordered eating may be helpful in developing novel treatments for both ADHD and binge eating.